2019
DOI: 10.1016/j.jot.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid fracture fixation systems developed for orthopaedic applications: A general review

Abstract: Orthopaedic implants are applied daily in our orthopaedic clinics for treatment of musculoskeletal injuries, especially for bone fracture fixation. To realise the multiple functions of orthopaedic implants, hybrid system that contains several different materials or parts have also been designed for application, such as prosthesis for total hip arthroplasty. Fixation of osteoporotic fracture is challenging as the current metal implants made of stainless steel or titanium that are rather rigid and bioinert, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 113 publications
(155 reference statements)
0
56
0
2
Order By: Relevance
“…In addition to aforementioned methods to enhance corrosion resistance and mechanical strength in Mg‐based metals, the development of a Mg‐based hybrid system may be another promising strategy to develop Mg‐containing implants suitable in high weight‐bearing skeletal sites 18,45. Our concept is to combine Mg‐based implants, which promote bone regeneration, with permanent metals that firmly fix fractures in high weight‐bearing skeletal sites 105. As proof‐of‐concept studies, the treatment of challenging bone diseases such as osteoporotic fractures, atypical femoral fractures, and long bone distraction has been tested in animals with innovative Mg‐based hybrid fixators.…”
Section: The Potential Use Of Mg‐based Hybrid Implants At High Weightmentioning
confidence: 99%
“…In addition to aforementioned methods to enhance corrosion resistance and mechanical strength in Mg‐based metals, the development of a Mg‐based hybrid system may be another promising strategy to develop Mg‐containing implants suitable in high weight‐bearing skeletal sites 18,45. Our concept is to combine Mg‐based implants, which promote bone regeneration, with permanent metals that firmly fix fractures in high weight‐bearing skeletal sites 105. As proof‐of‐concept studies, the treatment of challenging bone diseases such as osteoporotic fractures, atypical femoral fractures, and long bone distraction has been tested in animals with innovative Mg‐based hybrid fixators.…”
Section: The Potential Use Of Mg‐based Hybrid Implants At High Weightmentioning
confidence: 99%
“…In order to overcome this limitation, surface treatment technologies can be used to attain bioactive surfaces on Ti substrates [ 40 , 41 , 42 , 43 ]. The macro-scale, micro-scale, and nano-scale morphology of the implant surfaces have a crucial influence on the early bone formation and fixation [ 16 , 44 , 45 ]. Most titanium implant surfaces with certain roughness characteristics were fabricated through mixed technologies (e.g., grit-blasting, acid-etching).…”
Section: Introductionmentioning
confidence: 99%
“…Stainless steel and titanium are current metals used as bioinert and permeant Class-III implants for orthopaedic applications. Recently, bioactive or biodegradable metals have attracted great attention in research and development (R&D) of biomaterials for clinical applications [1][2][3][4]. Our recent clinical work showed that the bone grafting fixation using biodegradable pure Mg screw was beneficial for successful fixation of bony flap used for treatment of osteonecrosis of the femoral head (ONFH) in patients with steroid-associated osteonecrosis https://doi.org/10.1016/j.biomaterials.2020.119828 Received 4 October 2019; Received in revised form 7 January 2020; Accepted 25 January 2020 (SAON) where bony flap displacement was avoided and local bone density was increased accompanied by Mg-screw degradation, partially explained by the biologic effects of degraded Mg ions, yet like many available related clinical studies the scientific or mechanistic evidence was lacking [5].…”
Section: Introductionmentioning
confidence: 99%